PEMBELAJARAN ENSAMBEL MUSIK DI SMP NEGERI 02 SUNGAI AUA KABUPATEN PASAMAN BARAT - Alawiyah, Tuti; Lumbantoruan, Jagar (SENDRATASIK UNP, 2019)
AbstrakThe study aims to describe the learning of musical ensembles in SMP Negeri 02 Sungai Aua, Pasaman Barat Regency. The type of research was qualitative with using descriptive analysis method. The object of this research were students and teacher in SMP Negeri 02 Sungai Aua, Pasaman Barat Regency in teaching and learning activities of cultural art (music art) with using a recording instrument which were involving 20 students of calss VII 2 in odd semester 2019/2020. This research instrument was the research. Techniques of data collection were done by conducting observations, library studies, document studies, interviews.Based on results of this study, it was concluded that the learning of the recorder ensemble is done well, but the results are not good. It is seen in term of the making and preparation of lesson plan by the teacher and found a mismatch between basic competencies with the formulation of learning objectives that must be achieved by the students. Furthermore, the subject material is not in accordance with fact, concept and procedure. The teacher does not apply the methods, strategies, approaches, techniques properly. In playing musical instrument, the teacher does not revise or correct mistakes that are made by the students in the learning of the recorder which is about fencing, blowing or both at once. The teacher does not do tone training in the interval because the teacher only often trains the students with sequential scales. It can be proven by the results of the daily practice test evaluation, the students scores are obtained 80 which based on the SKBM there are 9 of 20 students who have completed. It means that the total percentage of completeness obtained in class VII 2 is 49%.Â Kata Kunci: Ensamble, muzik, recorder.Â